EPISTEMOLOGI KEILMUAN BARU DI PERGURUAN TINGGI KEAGAMAAN ISLAM NEGERI (TRANSFORMASI DARI STAIN/IAIN MENJADI UIN) - Asiyah, - (Madania: Jurnal Kajian Keislaman, 2016)
New Scientific Epistimology in State Collage for Islamic Studies: a ransformation from STAIN/IAIN to UIN. Historically, there is an academic anxiety for graduates’ fate of PTKIN if there are no integrated religious sciences with general sciences. Based on the fact, many scientific studies in PTKIN are only worth with theabstract, not empirical-historical. The academic’s anxieties are observed based on Ian G Barbour’s approach on the scientific assessment. The result is that the integrated-scientific epistemology is needed in PTKIN which has given the spirit and direction of the institutional transformation of STAIN /IAIN to UIN that has been successfully initiated by UIN Maliki of Malang, UIN Sunan Kalijaga Yogyakarta, and UIN Syarif Hidayatullah Jakarta. Epistemology of science recently developed at three UIN (-s) is part of development trend of an integrated approach of two sciences that Ian G Barbour stated. The integration approach emerges the newscientific epistemology such as in UIN Yogyakarta known as spider webs of Horizon scientific Teoantroposentric-Integralistik and in UIN Maliki known as clumps of trees.